Lipoprotein(a) throughout life in women - Pablo Corral; María Gabriela Matta; Carlos Aguilar-Salinas; Roopa Mehta; Gabriela Berg; Massimiliano Ruscica; Laura Schreier (American Journal of Preventive Cardiology)
Lipoprotein (a) [Lp(a)] is a lipoprotein with multiple deleterious characteristics and is a recognized cardiovascular (CV) risk factor. The pro-atherogenic, pro-thrombotic, and pro-inflammatory features of Lp(a) are associated not only with atherosclerotic vascular disease but also with aortic valve calcification and all-cause mortality. One of the most interesting aspects of Lp(a) is that its level is determined by genetics in more than 90% of cases, with lifestyle habits having very little influence. Therefore, the recommendation is to test it, at least, once in a lifetime. Contrary to previous beliefs, evidence in recent decades has shown that women have the same or even greater CV risk than men of the same age, attributed to female sex hormones. Different stages of a woman's life can impact on Lp(a) levels, from newborn to menopause, including other critical moments such as menarche and pregnancy. The main objective of this review is to describe and analyze the effect of different specific periods of a woman's life on Lp(a) levels and the potential clinical relevance on their CV risk.